Premisser för hållbarhet i den finländska utbildningen av lärare inom småbarnspedagogik - En kritisk granskning av visioner och verklighet - Ann-Christin Furu; Lili-Ann Wolff; Liisa Suomela (Utbildning & Demokrati)
Finnish Early Childhood Education and Care (ECEC) should, according to national policy documents and curricula, promote sustainable development and a sustainable life style. Early childhood educators play a key role in implementing strategies of sustainability in ECEC. This implies that sustainability should have a prominent position in early childhood teacher education. However, this is not the case. The aim of this article is to present how sustainability is formulated in Finnish policy documents as well as the premises for sustainability education in early childhood teacher education. Methodologically the study builds on a triangulation of three types of research material; national policy documents, a study of teacher students’ understanding of the concept of sustainable development, and a survey concerning courses on sustainability in early childhood teacher education. The results show a discrepancy between the vision and implementation of sustainability in Finnish early childhood teacher education. Based upon the study’s findings, we discuss how sustainability could be reinforced in early childhood teacher education.